Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior pada Perawat Rumah Sakit Dewi Sri Karawang - Junaedi, Ahmad; Suroso, Suroso; Maman Mulya Karnama (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to determine how Job Satisfaction and Organizational Commitment Influence Organizational Citizenship Behavior in Nurses at Dewi Sri Karawang Hospital. This study uses Verification, the sample in this study was 102 respondents, a saturated sample type, taking the entire population as a sample. Data was obtained using a liket scale news distributed directly face to face. The data analysis method used Multiple Linear Regression Analysis using SPSS V24. The results of this study showed that Job Satisfaction Variables partially had a positive and significant effect on Organizational Citizenship Behavior and Organizational Commitment partially had a positive and significant effect on Organizational Citizenship Behavior. Job Satisfaction and Organizational Commitment simultaneously had a positive and significant effect on Organizational Citizenship Behavior in Nurses at Dewi Sri Karawang Hospital.   Keywords: Job              Satisfaction,Organizational Commitment, Organizational